Shade tolerance response of legumes in terms of biomass accumulation, leaf photosynthesis, and chlorophyll pigment under reduced sunlight. Issue 1 (11th November 2022) - Umesh, Mathada Rangappa; Angadi, Sangamesh; Begna, Sultan; Gowda, Prasanna; Prasad, P. V. Vara
Abstract: Legumes have a distinct morpho‐physiological response to reduced sunlight, but their capacity to adapt to the levels of shading due to intercropping systems is not sufficiently understood. Such adaptation to shade—60% of full sun in terms of physiological attributes—was examined in cowpea ( Vigna unguiculata Savi), lablab ( Lablab purpureus Adans.), lima bean ( Phaseolus lunatus ), pigeonpea [ Cajanus cajan (L.) Millsp.], and pole bean ( Phaseolus vulgaris ). Although the capacity of photosynthetic machinery decreased under shade, the capacity continued to exceed the actual rate of photosynthesis. Compared with those under full sun, leaves under shade were thinner (specific weight only 56% of that under full sun), larger (surface area greater by 54.7%), and recorded a 15% higher leaves/stem ratio (by weight) and a 25.6% higher leaves/total dry weight ratio. However, the concentration of chlorophyll pigments per unit weight and per unit surface area was significantly higher in leaves under shade. Water stress was probably higher for leaves under full sun given the higher canopy temperatures and lower relative water content. At final biomass harvest, across the species shading has reduced the biomass 32% in 2009 and 34.6% in 2010 over unshade. Biomass was greater in lima bean (413 g m −2 ), and pigeonpea (408 g m −2 ) then lowest in lablab (180 g m −2 ) and cowpea (216 g m −2 ). Of the five legumes tested, lablab and cowpea showed the greatest tolerance to shade and therefore are better suited to the low‐light environment of intercropping. Core Ideas: Shading has significant influence on dry matter production and distribution and leaf morphology. Photosynthetic rate, chlorophyll pigments, and fluorescence of legumes were significantly influenced by shade. Morpho‐physiologically superior legumes under shade may fit for low light environments like intercropping system.